Factors Affecting Safety Performance: Case Study At Pt Pamapersada Nusantara - Muhammad Nabawi; A Izzuddin Abdissalam; Anita Maharani; Lidya Lidya (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The purpose of this study is to see the impact that safety performance can have on technical competencies, non-technical competencies, technical training and non-technical training Design/methodology/approach: The research method referred to in this study is quantitative research, and the object of this research is PT. Pamapersada Nusantara, further using 89 respondents as a research sample, refers to the structural equational modelling model. Findings: The results showed that the respondents considered that technical training had nothing to do with safety performance, while other hypotheses were proven. Research limitations/implications: Although we found that technical competency and non-technical competency influence safety performance, it still need further exploration in order to explore other factors that influence safety performance; also, there will be a necessity for research to explore within mining companies Practical implications: The managerial implication of this research is that the company can evaluate the technical training implemented, which is related to the readiness of the instructor, the implementation of classroom learning activities, simulator activities, field practice activities, the content of the material following the training objectives, and the benefits felt by employees who have attended technical training. Originality/value: This paper originated from exploring within one particular mining company Paper type: Research Paper